Association between autophagy and acute pancreatitis - Zhang, Tao; Gan, Yu; Zhu, Shuai (Frontiers in Genetics, 2023)
Autophagy pathway involves maintaining intracellular homeostasis by regulating the degradation of cytoplasmic components. Disfunction of autophagic process has been confirmed to be critical mechanism in many diseases, including cancer, inflammation, infection, degeneration and metabolic disorders. Recent studies have shown that autophagy is one of the early events in acute pancreatitis. Impaired autophagy promotes the abnormal activation of zymogen granules and results in apoptosis and necrosis of exocrine pancreas. Furthermore, multiple signal paths involve progression of acute pancreatitis by regulating autophagy pathway. This article provides a comprehensive review of the recent advances in epigenetic regulation of autophagy and the role of autophagy in acute pancreatitis.